Evaluating synthetic substitutes to reduce illegal harvesting and support species recovery - Aditya Shekhar Malgaonkar; Gareth Whittington‐Jones; Tristan Dickerson; Maswabi Lishandu; Sarah Davies; Zoe Woodgate; Xia Stevens; Choolwe Mulenga; Gift Mulenga; Mathew Phiri; Lucky Mulenga; Manyando Mukela; et al. (Conservation Biology, 2026)
Providing synthetic substitutes is a widely promoted strategy to shift consumer demand away from wildlife products derived from threatened species. Yet, there is little evidence on whether product substitution prevents illegal or unsustainable harvesting and contributes to the recovery of threatened populations. Drawing on the Furs for Life Zambia initiative, which supplied synthetic furs known as heritage furs to replace leopard furs traditionally worn during Lozi royal ceremonies in western Zambia, we devised a way to test the effects and causal mechanisms of substitution. Guided by the EMMIE (effect, mechanisms, moderators, implementation, and economic cost) framework commonly used in crime prevention evaluations, we triangulated data from semistructured questionnaires, law enforcement patrols, court records, camera‐trap monitoring of leopards ( Panthera pardus ), and stakeholder interviews conducted from 2018 to 2024. We used qualitative analyses and the general elimination method to assess plausible alternative explanations for leopard recovery. By 2024, adoption of synthetic furs among leopard fur users exceeded 80%, and self‐reported ownership of authentic leopard furs declined by 78%. Patrol detections of leopard poaching incidents decreased, and camera‐trap density estimates increased from an average of 2.7 to 3.8 leopards per 100 km 2 across the focal landscape. An integrated mechanism of change, derived from stakeholder perspectives, indicated that reduced demand from substitution was reinforced by concurrent counter‐poaching and counter‐trafficking operations. Our results provide the first empirical link between a demand‐reduction initiative based on synthetic substitutes and measurable population recovery of species.